Exploring Cultural Identities in Jean Rhys' Fiction. - Voicu, Cristina-Georgiana (De Gruyter, 2014)
Exploring Cultural Identities in Jean Rhys's Writings seeks to circumscribe Jean Rhys's work within a paradigm that reflects the search for a cultural identity so specific to postcolonial literature. The book carries out an examination of the relationship between hybrid identities, self and otherness and of several situations of existential ambivalence that work on the border between sign (colonial difference) and symbol (imperial authority).